A modified functional hoof trimming technique reduces the risk of lameness and hoof lesion prevalence in housed dairy cattle - Sadiq, Mohammed Babatunde; Ramanoon, Siti Zubaidah; Shaik Mossadeq, Wan Mastura; Mansor, Rozaihan; Syed Hussain, Sharifah Salmah (Elsevier, 2021)
The objective of this study was to compare the impact of the functional hoof trimming (HT) method to an adaptation that results in increased modelling of the weight bearing claw on time to lameness and lesion prevalence in housed dairy cows. A total of 418 non-lame cows at early and late lactation were enrolled in the study and randomly allocated into 3 groups: functional HT (TRIM1), adaptation method (TRIM2), and an untrimmed group (CON). Locomotion scores (LS; 5-point scale) and animal-based welfare measures were assessed monthly from enrolment until the following 270 days in milk. Cows were considered lame when 2 consecutive LS = 3, or any assessment with a score of 4 or 5. Kaplan-Meier analysis was used to evaluate the difference in time to lameness between the groups. Multivariable CC Cox regression models were fitted to assess associations between covariates and time to lameness event, while associated factors for lesion prevalence were estimated using logistic regression models. The incidence rate of lameness was 29.3 cases/100/month, with corresponding rates of 28.7, 15.8 and 42.8 cases/100/months, in TRIM1, TRIM2 and CON, respectively. Time to first lameness event was higher in TRIM2 (mean ± S.E; 8.26 ± 0.16, P = 0.03) than CON (7.32 ± 0.2) and tended to be higher than TRIM1 (7.83 ± 0.19; P = 0.07). The risk of new lameness event was higher in cows with low BCS (≤2.5) (Hazard ratio; HR = 1.5; 95 % CI 1.1–2.1), while trimming all feet was a protective factor (HR = 0.58; 95 % CI 0.38–0.90). The prevalence of hoof lesions in the study population was 36.3 %, with the highest prevalence in CON (45.6 %), followed by TRIM1 (34.6 %) and TRIM2 (28.1 %). Seventy-eight per cent of hoof lesions were non-infectious and the majority of cows with hoof lesion in TRIM1 (72.3 %), CON (74.6 %) and TRIM2 (55.6 %) were lame. The odds of having a non-infectious hoof lesion were higher in CON (OR = 2.1; 95 % CI 1.2–3.7) compared to TRIM2, and in cows with hock injury (OR = 3.1; 95 % 1.1–9.7) relative to healthy hock, and tended to be higher in cows with low BCS (P = 0.09) relative to those with moderate BCS. Our results suggest that the adaptation to the functional method reduced the risk of lameness during lactation, however, proper management of under-conditioned cows is equally important.